Imaging in paediatric rheumatology: Is it time for imaging?. Issue 4 (August 2016) - Collado, Paz; Malattia, Clara
Abstract: Juvenile idiopathic arthritis (JIA) is a heterogeneous group of arthritides characterized by chronic synovial inflammation that can lead to structural damage. The main objective of JIA therapies is to induce disease control to avoid disability in childhood. The advances in therapeutic effectiveness have created a need to search for imaging tools that describe more precisely disease activity in children with JIA. Musculoskeletal ultrasound and magnetic resonance imaging have demonstrated to be more sensitive than clinical examination in early detection of synovitis. These modalities can detect both inflammatory and destructive changes. The unique characteristics of the growing skeleton and a scarce validation of imaging in children result in important challenges in evaluating paediatric population. This review describes indications and limitations of these imaging techniques and suggests some advices for a rational use in the management of JIA in clinical practice.